IDENTIFIKASI KERUSAKAN PADA TEGAKAN NYAWAI (Ficus variegate Blume) DI KHDTK RIAM KIWA DESA LOBANG BARU KECAMATAN PENGARON KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Dony Anggara; Normela Rachmawati; Dina Naemah (Universitas Lambung Mangkurat, 2020)
This study aims to identify the types of damage found in the Nyawai stand using a purposive sampling method in order to obtain a description of the desired data as many as three plots size of 27x27 meters. The results obtained showed that the location of the greatest damage was found in the root, upper stem and lower stem. The type of damage that attacks the most tree stands is open wounds, fungi and cancer. The canopy condition of the Nyawai stand shows normal leaves. The most dominant type of damage in the tree stands is open wounds with 135 stands, mushrooms as many as 99 stands and cancer as many as 34 stands.